2003
DOI: 10.1093/aje/kwg020
|View full text |Cite
|
Sign up to set email alerts
|

Allergy, Atopy, and Cancer: A Prospective Study of the 1981 Busselton Cohort

Abstract: The associations among certain allergic disorders, atopy upon skin-prick testing, and specific cancers were evaluated in a prospective study. Information regarding history of asthma and hay fever was collected by questionnaire from 3,308 cancer-free participants in the 1981 Busselton Health Survey. A subset of 1,005 participants also underwent skin-prick testing. The cohort was followed for a new diagnosis of cancer or death until the end of 1999. Cox proportional hazards regression analysis was used to estima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
141
2
12

Year Published

2005
2005
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(166 citation statements)
references
References 22 publications
11
141
2
12
Order By: Relevance
“…The increased risks in cancers of the colon, liver, and pancreas have not been reported earlier and most earlier studies have shown a reduced risk or risk close to unity (Vesterinen et al, 1993;Talbot-Smith et al, 2003;Turner et al, 2005). The excess of colon cancer increased with the number of hospital admissions and the SIR was 1.99 for those hospitalised more than 5 times, highest for any cancer, suggesting a true aetiological link.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…The increased risks in cancers of the colon, liver, and pancreas have not been reported earlier and most earlier studies have shown a reduced risk or risk close to unity (Vesterinen et al, 1993;Talbot-Smith et al, 2003;Turner et al, 2005). The excess of colon cancer increased with the number of hospital admissions and the SIR was 1.99 for those hospitalised more than 5 times, highest for any cancer, suggesting a true aetiological link.…”
Section: Discussionmentioning
confidence: 73%
“…An increase in oesophageal and stomach cancers was reported earlier and partly attributed to gastro-oesophageal reflux caused by b-adrenergic medication (Ye et al, 2001). A significant increase of rectal cancer has been reported among Finnish women (Vesterinen et al, 1993), whereas an excess of prostate cancer has been reported in cohort studies from Japan and Australia (Ohrui et al, 2002;Talbot-Smith et al, 2003).…”
Section: Discussionmentioning
confidence: 88%
“…In particular, a recent case-control study conducted in Finland (9) reported an inverse risk association between overall NHL and positive specific IgE (OR, 0.68; 95% CI, 0.58-0.80) with risk associations for some (CLL, follicular, and lymphoplasmacytic) but not all (diffuse, marginal zone, and T cell) individual NHL subtypes being similar to those reported in the current study. On the other hand, some studies have shown no, or even an opposite, association (11,27).…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, there are few prospective studies that can address this question, and those that exist tend to be too small to be conclusive. Prospective studies based on biomarkers have reported no association between total serum immunoglobulin E (13) or skin hypersensitivity (14) and subsequent NHL risk. A recent Swedish linkage study found a statistically significant 4-fold increased risk of NHL among women diagnosed as atopic by skinprick testing (15).…”
Section: Atopic Conditions and Associated Factorsmentioning
confidence: 99%